Rancang Bangun dan Uji Kinerja Mesin Oil Skimmer Disk Type Berdasarkan Volume dan Kadar Ph Pada Cairan Pendingin Mesin CNC Milling Hurco Seri Vm10 - Ipung Kurniawan; Pujono; Joko Setia Pribad Pribad; Agus Santoso; Ariq Rafi Ibrahim; Hilmam Zulmi Adha (Infotekmesin, 2026)
Modern machining processes heavily rely on liquid coolants to extend the life of cutting tools; however, water-soluble coolants are susceptible to oil contamination, which degrades their quality. This research aims to design the form and details of a disc-type oil skimmer machine, perform the necessary machine element calculations, and test the results. The design process utilizes the VDI 2222 systematic approach with the aid of Autodesk Inventor 2025 software, supported by literature and field studies. The calculation results indicate a required motor power of 0.042 HP, a minimum shaft diameter of 7.2 mm, and a dynamic bearing load of 5.868 N. The frame strength analysis also ensures safety, with a maximum stress of 15.19 N/mm², well below the allowable limit of 79,2 N/mm². In conclusion, this design yields a viable and safe oil skimmer for implementation on the Hurco VM10 series CNC Milling machine, complete with detailed working drawings and an optimal speed of 80 rpm for separating oil from the coolant.